The Implementation of Solar Roof Panel Responding to Sustainable Society: A case study of Tropical Medicine Hospital, Bangkok, Thailand - Chomming, Sawake; Kliengchuay, Wissanupong; Niempradit, Sarima; Srimanus, Wechapraan; Phonphan, Walaiporn; Tantrakarnapa, Kraichat (Journal of Posthumanism, 2025)
Climate change is a critical issue worldwide due to the increasing of Carbon Dioxide emission and its consequence. Carbon Dioxide is classified as one of Green House Gas emissions that linked to Climate Change. The Green and Clean hospital approach is one strategy for Climate Change mitigation and adaptation measures. This study attempts to determine the greenhouse gas emissions (CO2) from solar power generated on the rooftop building as well as the feasibility of generating 187,778 kW of electricity from solar energy at the Tropical Medicine Hospital, Bangkok. According to the study’s findings, 321,906.34 GWh/year of electricity might be produced annually, which would result in a monthly reduction of roughly 164,204.43 tCO2e/year in greenhouse gas emissions. The production of electricity and used in the hospital can support Thailand to be sustainable for energy usage and respond to the concept of clean and green hospital issued by Ministry of Public Health, Thailand.